Is it or is it not? Lessons learned from a case of suspected vaccine strain measles. (19th March 2020) - Lord, Heidi; Kok, Jen; Fletcher, Stephanie; Alexander, Kate
Abstract: Objective: Measles continues to be a threat to Australia. While post‐eradication risks are low, imported measles cases from overseas travellers who are non‐immune can cause small outbreaks. This case report discusses the challenge of identifying wild‐type measles in an individual who was recently vaccinated with measles‐containing vaccine (MCV). Methods: A positive polymerase chain reaction (PCR) result for measles for an adult who had recently received a measles‐containing vaccine was notified. Investigation revealed no known epidemiological link, recent overseas travel or contact with recent measles cases during the incubation period. Results: The results of the initial sequencing to distinguish between wild‐type and vaccine‐strain measles were inconclusive. A decision was made to re‐run the genotyping, collect additional specimens and quarantine the case until a definitive result was obtained. Sequencing and genotyping revealed that this indeed was a wild‐type measles strain. Conclusions: Changing epidemiology of measles means distinguishing between wild‐type and vaccine–strain measles has become a new challenge. Implications for public health: The reflection of the public health management of this case has provided a valuable teaching tool for public health professionals globally, particularly in low incidence measles countries.